Analysis of parameter sensitivity on dynamics of satellite separation. (September 2015) - Cui, Delin; Zhao, Jieliang; Yan, Shaoze; Guo, Xiaosong; Li, Junlan
Abstract: Dynamic characteristics of satellite separation are synthetical results of various influencing factors. However, there have been few quantitative investigations on impact evaluation of crucial parameters on dynamics of satellite separation. In this paper, an improved dynamic simulation model of the typical satellite separation system considering the flexibility of interface rings is established based on the authors׳ previous work. The dynamic-envelope radius of seventh V-segment and the shock response amplitude in horizontal section of SRS curves are, respectively, taken as evaluation index to perform the analyses of parameter sensitivity. Subsequently, an improved Response Surface Methodology (RSM) for analyzing parameter sensitivity of dynamics of satellite separation is proposed. Finally, the impact evaluations of different parameters are carried out, respectively, by performing the sensitivity analysis on dynamic-envelope of clamp band and satellite separation shock responses to determine the most important parameters that significantly influence the dynamic characteristics. It is revealed from the studies that the parameter which has the most prominent effect on the dynamic-envelope of clamp band is the stiffness of lateral-restraining spring. While for the axial and radial separation shock responses, the preload of clamp band and the density of V-segments are respectively the most influential parameters. The research results in the paper can provide a reference for the initial engineering design of the clamp band joint of satellite separation systems to guarantee a secure and reliable separation event. Highlights: An improved dynamic simulation model of the satellite separation system is built. A revised Response Surface Method for analyzing parameter sensitivity is proposed. The impact evaluations of parameters on satellite separation are carried out. The conclusions provide a reference for engineering design of clamp band system.